A Study of the Socioeconomic Impact of Mobile Phones on SMEs in the Waterloo Community, the Western Rural District of Sierra Leone - Hassan Elsan Mansaray (Randwick International of Social Science Journal, 2021)
To assess the impact of mobile phones on small and medium enterprises (SMEs) in the Waterloo Community, the researcher used qualitative research methods to do the study. It is selected with the intention of evaluating the socioeconomic impact on the use of mobile phones in the transport, Sand and stone mining as well as general merchandize/petty trading activities in the Waterloo community. Hence, simple random sampling technique was applied in selecting the number of participants that were involved in the study. The study discovered that the SMEs have contributed to socioeconomic development at certain level through the use of mobile phones. The impact of mobile phones in the Waterloo community involved: precise accounting and bookkeeping, making payments and collections, selling of products, and services to customers, connecting people, and increase business network opportunities and jobs creation. The study further revealed the challenges faced by SMEs in their daily operations in the Waterloo community for example, increased competition from large firms, and multinational corporations, the ability to adjust to fast changing market demand, technological capacity, and change limitations linking knowledge, innovation, and creativity. Other challenges include lack of previous experience to run the SMEs, poor planning, no proper markets assessment, uncommercialized products, scanty marketing skills and lack of good corporate governance.